Festivals in Age of AI: Smarter Crowds, Happier Fans - João M. Lopes; Ilda Massano-Cardoso; Camila Granadeiro (Tourism and Hospitality)
Artificial intelligence (AI) stands out as a transformative force in various sectors, offering both new opportunities and challenges. In tourism and music events, AI has proven to be a powerful tool for improving the attendee experience, personalizing artist recommendations, optimizing event logistics in real time, and enhancing audience interaction through virtual assistants and immersive visual effects, thus highlighting its transformative potential. This study aims to analyze the impact of applying AI to the experience of consumers at music festivals. In particular, the research examines the impact of AI on the quality of information delivered, the extent of consumer engagement with brands at the event, and the level of trust in the technology. A quantitative methodology was used, collecting 400 responses from Portuguese consumers who attended music festivals. The results show that the quality of information and the AI positively influence customer engagement with the brand. Greater customer engagement, in turn, increases the willingness to use AI solutions. Trust in AI is significantly shaped by the quality of the information and the reliability of the system, which further promotes electronic word-of-mouth (eWOM) and the willingness to adopt AI. In addition, eWOM plays a key role in encouraging the use of AI technologies. Finally, memorable tourist experiences positively influence the willingness to adopt AI, underlining the importance of experiential factors in promoting adoption. These results highlight the interconnected roles of information quality, trust, involvement, and user experiences in shaping attitudes toward artificial intelligence applications. This study expands the literature by analyzing how AI-driven information quality influences consumer trust and engagement, thus emphasizing the need to optimize these factors for better festival strategies. It highlights the link between trust and positive eWOM, showing that trust based on high-quality information enhances the festival’s reputation and attracts participants. A key contribution is its exploration of how trust and eWOM influence AI adoption at future festivals, which offers insights to boost credibility and acceptance. Lastly, it provides strategic guidelines that improve attendee experience and festival management.